The Effect of Motivation, Loyalty and Competence on Employee Performance at Pharmaceutical Wholesalers in Palembang City - Afriyan Gunadi; Fatimah; Trisniarty A. M (International Journal of Marketing & Human Resource Research, 2022)
This study aims to determine the effect of motivation. loyalty and competence on employee performance jointly and partially at a pharmaceutical wholesaler company in the city of Palembang. The variables in this study were motivation, loyalty, and competence in performance. The population in this study was 1687 employees of pharmaceutical wholesalers in Palembang city with 243 samples. The sampling technique in this research was purposive sampling. The results of data analysis in this study showed that together motivation, loyalty, and competence variables had a significant effect on employee performance of the pharmaceutical wholesaler company in the city of Palembang. Individually the motivation variable has a significant impact on performance. The loyalty variable has a significant impact on performance and the competency variable significantly affected the performance of a pharmaceutical wholesaler company in the city of Palembang.